Constructing the Asia Pacific Regional Cooperation and integration index a panel approach. - Cyn-Young,Park (Metro Manila, Philippines Asian Development Bank, 2018)
This paper employs a panel approach in constructing the Asia Pacific Regional Cooperation and Integration Index (ARCII) to strengthen the indexs ability to track the progress of economic integration in the region over time. Of the six dimensions featured in the ARCII, trade and investment and movement of people are the main drivers of regional integration, while the money and finance dimension was the weakest link. Findings suggest the pace of integration in 2006 to 2016 was steady, driven by trade and investment. Modest gains in regional integration were made across most economies. Meanwhile, Asia comes second to the European Union (EU) in progress on regional integration, but in recent years several Asian economies have broken through to the top tier dominated by the EU economies.
Keywords: Public-private sector cooperation -- Asia -- Finance; Industry and state; Electronic books